2017
DOI: 10.1371/journal.pgen.1007010
|View full text |Cite
|
Sign up to set email alerts
|

Dynein light chain regulates adaptive and innate B cell development by distinctive genetic mechanisms

Abstract: Mechanistic differences in the development and function of adaptive, high-affinity antibody-producing B-2 cells and innate-like, “natural” antibody-producing B-1a cells remain poorly understood. Here we show that the multi-functional dynein light chain (DYNLL1/LC8) plays important roles in the establishment of B-1a cells in the peritoneal cavity and in the ongoing development of B-2 lymphoid cells in the bone marrow of mice. Epistasis analyses indicate that Dynll1 regulates B-1a and early B-2 cell development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
(98 reference statements)
1
23
0
Order By: Relevance
“…Other examples of the effect of BIM on B cell development include the partial or complete rescue of B cell development defects of IL-7-deficient or IL-7 receptor-deficient mice ( 6 , 8 ), dicer -deficient mice ( 33 ), or Asciz -deficient mice ( 29 ) by germline Bim KO. Indeed, we recently found that conditional Bim deletion can fully rescue the B cell developmental defects of Mb1-Cre Dynll1 -deleted mice ( 17 ), which are mechanistically and quantitatively similar to those observed in the Mb1-Cre Asciz -deleted mice. This indicates that BIM exerts its effects on B cell development under pathological conditions, at least during B lymphomagenesis, also in a cell-intrinsic manner in the B lymphoid lineage.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Other examples of the effect of BIM on B cell development include the partial or complete rescue of B cell development defects of IL-7-deficient or IL-7 receptor-deficient mice ( 6 , 8 ), dicer -deficient mice ( 33 ), or Asciz -deficient mice ( 29 ) by germline Bim KO. Indeed, we recently found that conditional Bim deletion can fully rescue the B cell developmental defects of Mb1-Cre Dynll1 -deleted mice ( 17 ), which are mechanistically and quantitatively similar to those observed in the Mb1-Cre Asciz -deleted mice. This indicates that BIM exerts its effects on B cell development under pathological conditions, at least during B lymphomagenesis, also in a cell-intrinsic manner in the B lymphoid lineage.…”
Section: Discussionsupporting
confidence: 67%
“…The following reagents were used for cell staining: B220-APC (eBioscience™, 17-0452-83), B220-FITC (Biolegend, 103206), BP1-PE (BD, 553735), CD11b-pacific blue (eBioscience™, 48-0112-82), CD8-APC (eBioscience™, 17-0081-82), CD4-PE(eBioscience™, 12-0041-83), CD5-FITC (BD, 553021), CD11b-APC-Cy7 (BD, 557657), CD19-APC eFluor780 (eBioscience™, 47-0193-82), CD19-PerCP-Cy5.5 (eBioscience™, 45-0193-82), CD21-PE (Biolegend, 123410), CD23-biotin (BD, 553137), CD24-FITC (BD, 561777), CD43-biotin (BD, 553269), CD43-PE (BD, 553271), GR1-biotin (eBioscience, 13-5931-85), IgD-eFluor450 (eBioscience™, 48-5993-82), IgM-PE-Cy7 (BD, 552867), Brilliant Violet 605™ Streptavidin (Biolegend, 405229), and propidium iodide (Sigma, P4864-10ML). Our gating strategies for staining of bone marrow B lymphoid fractions according to Hardy et al ( 16 ), total and mature splenic B cell numbers, and peritoneal cavity B-1a cell analyses were recently described ( 15 , 17 ). Hardy fractions were gated as follows: A, B220 + CD43 + CD24 low BP1 − ; B, B220 + CD43 + CD24 high BP1 − ; C, B220 + CD43 + CD24 low BP1 + ; C’, B220 + CD43 + CD24 high BP1 + ; D, B220 + CD43 − IgM − IgD − ; E (immature B cells), B220 + , CD43-, IgM + , IgD − ; F (recirculating B cells), B220 + , CD43 − , IgD + .…”
Section: Methodsmentioning
confidence: 99%
“…Mutant phenotypes in Drosophila , developing mouse B lymphocytes, and cultured cells are rescued by ectopic overexpression of LC8, demonstrating that the observed defects of ASCIZ knockouts are due to ASCIZ regulation of LC8 expression ( Goggolidou et al, 2014b ; Jurado et al, 2012b ; Zaytseva et al, 2014 ). In addition, it has recently been shown that a conditional knockout of LC8 almost perfectly copies the corresponding phenotypes of ASCIZ knockouts in mouse B cell development and B cell lymphomagenesis ( King et al, 2017 ; Wong et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dynll1 is a subunit of the dynein motor complex and is known for its role in vesicular transport (36). However, more recent work has shown that it may participate in other processes, (36,37,(49)(50)(51)(52). These additional roles may require Dynll1 to interact with additional partners in different organelles.…”
Section: Discussionmentioning
confidence: 99%